A systematic literature review of math interventions across educational settings from early childhood education to high school - Svane, Riikka Pauliina; Willemsen, Marinka Marianne; Bleses, Dorthe; Krøjgaard, Peter; Verner, Mette; Nielsen, Helena Skyt (Frontiers in Education, 2023)
Early math skills lay the foundation for children’s long-term academic success. An increasing number of randomized controlled math interventions have been carried out across educational settings. The aim of the present systematic review was to identify the distribution of the randomized controlled math interventions conducted between 2001 to 2021 in educational settings across Early Childhood Education (ECE) up to high school among various sample types , and to describe their central features at each educational setting separately. Based on the knowledge gaps exposed through the systematic review, we aimed to discuss where and how future math interventions are still needed in order to improve optimize all children’s math skill developments across educational settings and sample types from early on. A total of n = 75 math interventions meeting the inclusion criteria using the PRISMA-guidelines were identified, of which the majority of them were executed in the elementary school, mostly targeting at-risk children. It is proposed that there is still a large potential of promoting children’s math skills from early on in the ECE settings, utilizing both teachers and parents, among at-risk and non-at-risk samples.